2019
DOI: 10.5194/acp-19-15339-2019
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the anthropogenic NO<sub><i>x</i></sub> emission trend over the United States during 2003–2017 from satellite observations: was there a flattening of the emission trend after the Great Recession?

Abstract: Abstract. We illustrate the nonlinear relationships among anthropogenic NOx emissions, NO2 tropospheric vertical column densities (TVCDs), and NO2 surface concentrations using model simulations for July 2011 over the contiguous United States (CONUS). The variations in NO2 surface concentrations and TVCDs are generally consistent and reflect anthropogenic NOx emission variations for high anthropogenic NOx emission regions well. For low anthropogenic NOx emission regions, however, nonlinearity in the anthropogen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 61 publications
3
25
0
Order By: Relevance
“…Based on calculations by 17 using a regional model, β is estimated to increase by a factor of ~2.2 when decreasing the anthropogenic emission from ~160 • 10 10 molec.cm −2 s −1 to 20 • 10 10 molec.cm −2 s −1 ; this translates into a 22% increase in β for the estimated emission decrease between 2005-2007 and 2015-2017 (factor of 1.7 according to US EPA 18 , in line with recent assessments 17,19,20 ). This change in β is in excellent agreement with our model results (+20%).…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Based on calculations by 17 using a regional model, β is estimated to increase by a factor of ~2.2 when decreasing the anthropogenic emission from ~160 • 10 10 molec.cm −2 s −1 to 20 • 10 10 molec.cm −2 s −1 ; this translates into a 22% increase in β for the estimated emission decrease between 2005-2007 and 2015-2017 (factor of 1.7 according to US EPA 18 , in line with recent assessments 17,19,20 ). This change in β is in excellent agreement with our model results (+20%).…”
supporting
confidence: 68%
“…This change in β is in excellent agreement with our model results (+20%). Only a small part of this change is due to chemical feedbacks, as pointed out by 17 . Using MAGRITTE model simulations for the years 2006 and 2016 (with identical meteorological fields and natural emissions for the two years in order to isolate the anthropogenic impact), we calculate that chemical feedbacks can increase β by only about 4-8% at the largest U.S. cities ( Supplementary Fig.…”
mentioning
confidence: 97%
“…Constraining HCHO has a significant influence on the chemical production of CO and the trend in Inv2 (Zheng et al, 2019). Tropospheric columns of OMI HCHO have been reported to keep increasing over China, likely due to significant increases in NMVOC emissions (Li & Wang, 2019; Shen et al, 2019). This could explain why CO emission estimates continue to decrease in Inv2, while Inv1 flattens out since the optimized emissions are overestimated to compensate for the underestimation of CO photochemical production.…”
Section: Comparison Of Emission Inventories and Inverse Modeling Estimentioning
confidence: 99%
“…They suggest that increases in the relative contribution of non‐anthropogenic background sources of NO x (e.g., lightning and soils) explain the discrepancy between trends in OMI NO 2 and the NEI inventory. Furthermore, several studies have reported that in rural areas, strong nonlinear relationships exist between anthropogenic NO x emissions and satellite NO 2 columns, implying that constraining NO x emissions by NO 2 satellite retrievals might lead to inaccurate estimates (Lamsal et al, 2011; Li & Wang, 2019; Vinken et al, 2014). Laughner and Cohen (2019) reported changes in NO x lifetime for many U.S. cities and suggested that accounting for this change in lifetime more accurately (for example, by using models with higher resolution) should help to improve emission trend estimates.…”
Section: Comparison Of Emission Inventories and Inverse Modeling Estimentioning
confidence: 99%
“…Some studies inferred NO x (Pison et al, 2007;Tang et al, 2013) and VOC emissions (Koohkan et al, 2013) from surface measurements. Konovalov et al (2006Konovalov et al ( , 2008Konovalov et al ( , 2010, Mijling et al (2012Mijling et al ( , 2013, van der A et al (2008), Lin et al (2012) and Ding et al (2017) have also shown that satellite observations are a suitable source of information to constrain NO x emissions. These regional inversions using satellite observations were often based on Kalman filter (KF) schemes (Mijling et al, 2012(Mijling et al, , 2013van der A et al, 2008;Lin et al, 2012;Ding et al, 2017).…”
mentioning
confidence: 99%